The wartime sisters [large type] - Loigman, Lynda Cohen (Thorndike Press, a part of Gale, a Cengage Company, 2019)
For fans of Lilac Girls, the next powerful novel from the author of Goodreads Choice Awards semifinalist The Two-Family House about two sisters working in a WWII armory, each with a deep secret. Loigman's strong voice and artful prose earn her a place in the company of Alice Hoffman and Anita Diamant, whose readers should flock to this wondrous new book.--Pam Jenoff, New York Times bestselling author of The Orphan's Tale The Wartime Sisters shows the strength of women on the home front: to endure, to fight, and to help each other survive. --Jenna Blum, New York Times and international bestselling author of The Lost Family and Those Who Save Us Two estranged sisters, raised in Brooklyn and each burdened with her own shocking secret, are reunited at the Springfield Armory in the early days of WWII. While one sister lives in relative ease on the bucolic Armory campus as an officer's wife, the other arrives as a war widow and takes a position in the Armory factories as a "soldier of production." Resentment festers between the two, and secrets are shattered when a mysterious figure from the past reemerges in their lives.